Distribution and characteristics of endometriotic lesions in South- Western Nigeria: A single institutional experience (2019)
Background: Endometriosis poses a significant burden mainly to women of child bearing age. Historically, endometriosis was thought to be of low prevalence among African women. However, recent studies have documented an increased prevalence than previously thought. This study aimed to determine the distribution and characteristics of endometriotic lesions among Nigerian women . Methods: A retrospective study of all histologically diagnosed cases of endometriosis from the records of the Department of Pathology, University College Hospital, Ibadan from 1st January, 1997 to 31st October, 2018.The age of the women, location and distribution of the lesions were analysed. Results: A total of 85 cases of endometriosis were diagnosed histologically in the period under review. The mean age was 35 years with an age range of 18 to 52 years. The most commonly affected age groups were those between 30-39 years (47.1%) and 20-29 years (30.6%). The most commonly affected site was the ovary (58.8%) followed by the umbilicus (11.9%) and fallopian tubes (9.4%). Fourteen patients (28%) had bilateral ovarian involvement. Left sided ovarian lesions predominated (61.1% versus 38.9%). Eighteen (21.2%) patients had lesions at more than one site frequently involving both ovaries. Conclusion: Endometriosis affected mainly women of childbearing age with particular predilection for the ovaries. Endometriosis affecting the umbilicus is not uncommon among Nigerian women.